Lesions to Lateral Prefrontal Cortex Impair Lexical Interference Control in Word Production - Piai, Vitória; Riès, Stéphanie K.; Swick, Diane (Frontiers in Human Neuroscience, 2016)
Speaking is an action that requires control, for example, to prevent interference from distracting or competing information present in the speaker’s environment. Control over task performance is thought to depend on the lateral prefrontal cortex (PFC). However, the neuroimaging literature does not show a consistent relation between left PFC and interference control in word production. Here, we examined the role of left PFC in interference control in word production by testing six patients with lesions to left PFC (centred around the ventrolateral PFC) on a control-demanding task. Patients and age-matched controls named pictures presented along with distractor words, inducing within-trial interference effects. We varied the degree of competing information from distractors to increase the need for interference control. Distractors were semantically related, phonologically related, unrelated to the picture name, or neutral (XXX). Both groups showed lexical interference (slower responses with unrelated than neutral distractors), reflecting naming difficulty in the presence of competing linguistic information. Relative to controls, all six left PFC patients had larger lexical interference effects. By contrast, patients did not show a consistent semantic interference effect (reflecting difficulty in selecting amongst semantic competitors) whereas the controls did. This suggests different control mechanisms may be engaged in semantic compared to lexical interference resolution in this paradigm. Finally, phonological facilitation (faster responses with phonological than unrelated distractors) was larger in patients than in controls. These findings suggest that the lateral PFC is a necessary structure in providing control over lexical interference in word production, possibly through an early attentional blocking mechanism. By contrast, the left PFC does not seem critical in semantic interference resolution in the picture-word interference paradigm.